Semen quality and sperm characteristics in broiler breeder cockerels fed vitamin E during hot season - Monsuru Oladimeji Abioja; Stephen Apuu; James Olamitibo Daramola; Mathew Wheto; Obafemi Foluso Akinjute (Acta Scientiarum: Animal Sciences, 2022)
Thirty-two Arbor Acres (AA) cockerels aged 27 weeks were used to determine the effect of vitamin E (VE) on the semen characteristics and sperm quality during hot season. The birds were fed diets containing 0, 50, 100 and 150mg VE kg-1 feed. There were 4 replicates and two birds per replicate. Semen collection was done thrice a week for three weeks in all birds. Dietary vitamin E significantly (p < 0.05) increased the semen volume (SV) and number of sperm cells (NS) in AA cockerels. CONTROL birds (0.71 mL) had lower SV than birds fed 150 mg VE (0.94 mL). Birds on 100 and 150 mg VE recorded similar NS, which was higher than 0 and 50 mg VE groups. The least NS was in the CONTROL group. Sperm abnormality gradually (p < 0.05) decreased as dietary VE increased from 0 to 150 mg. Significant (p < 0.01) effect of dietary VE was recorded in percentage live sperm (PLS). Semen from cockerels on VE treatment had higher PLS than the CONTROL. In conclusion, it may be beneficial to supplement the broiler breeder cockerel diet with VE up to 150 mg kg-1 feed during hot season as it increased SV, NS and PLS and decreased sperm abnormality.